Specifics of Implementation of Office Audit Inquiry of Economic Activity by the Staff of Financial and Tax Authorities of the Russian Federation - V. V. Firsov (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2019)
The article discusses the specifcs of the implementation of documentary audits of economic activities by employees of fnancial and tax authorities of the Russian Federation, which requires special attention from the entire legal and economic community and is one of the important policies of each state that respects rights and freedoms of citizens and protecting these rights by legal means.